THE FACTS AND MIRAGE OF INTEGRATING ARTIFICIAL INTELLIGENCE INTO THE JUDICIAL SYSTEM OF NIGERIA - DR ENYINNAYA N. OBOH (International Studies Journal)
The creation of machines that are able to learn, reason and perform activities in typical ways of human intelligence is becoming the state-of-the-art application in almost all human endeavour. It is acceptable as a means of relieving excessive workloads on human. The intrigue of these machines is that they are imbued with human intellect and are referred to as Artificial Intelligence (AI) due to the fact that they mimic human capabilities in reasoning, discovering meaning and or learning from past experiences. Their employment is revolutionizing all sectors of the world including the judicial sector. The doctrinal research approach is adopted in this study. It is manifest that the integration of AI in the complex Nigeria judicial system is feasible with identifiable benefits ranging from easy and quick access to justice, accurate legal research, efficiency and accuracy in legal processes and reduction of backlog cases while creating ample time for legal professionals to handle more strategic legal tasks. A technological framework to interface AI with judicial functions is what is required. Despite these benefits, the mirage of AI technology manifests in surmountable set-backs, such as lack of technological infrastructure, inadequate regulatory framework, societal and cultural acceptance, fear of job displacement, vulnerability to cyber-attacks and AI algorithms biases among others. However, fusing AI technology in Nigeria’s judicial system is an acceptable choice when compared to the benefits therefrom. It is recommended that a formidable legal and regulatory framework be developed in fulfilment of the provision of section 18 (2) of the Constitution of the Federal Republic of Nigeria to achieve a seamless AI integration in the justice system of Nigeria.